Prediction of the Minimum Film Boiling Temperature of Quenching Vertical Rods in Water Using Random Forest Machine Learning Algorithm - Alotaibi, Sorour; Ebrahim, Shikha; Salman, Ayed (Frontiers in Energy Research, 2021)
A great amount of research is focused, nowadays, on experimental, theoretical, and numerical analysis of transient pool boiling. Knowing the minimum film boiling temperature for rods with different substrate materials that are quenched in distilled water pools at various system pressures is known to be complex and highly nonlinear process. This work aims to develop a new correlation to predict the minimum film boiling temperature in the above process: Random Forest machine learning technique is applied to predict the minimum film boiling temperature. The approach trains a machine learning algorithm using a set of experimental data collected from the literature. Several parameters such as Liquid sub-cooling temperature, fluid to the substrate material thermo-physical properties (βf/βw), and system saturated pressure are collected and used as inputs, whereas is measured and used as the output. Computational results show that the algorithm achieves superior results compare to other correlation reported in the literature.